2010
DOI: 10.1111/j.1556-4029.2010.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Age Estimation by Calculation of Pulp–Tooth Volume Ratios Yielded on Clinically Acquired Cone Beam Computed Tomography Images of Monoradicular Teeth*

Abstract: Secondary dentine is responsible for a decrease in the volume of the dental pulp cavity with aging. The aim of this study is to evaluate a human dental age estimation method based on the ratio between the volume of the pulp and the volume of its corresponding tooth, calculated on clinically taken cone beam computed tomography (CBCT) images from monoradicular teeth. On the 3D images of 111 clinically obtained CBCT images (Scanora(®) 3D dental cone beam unit) of 57 female and 54 male patients ranging in age betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
131
6
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(164 citation statements)
references
References 52 publications
9
131
6
11
Order By: Relevance
“…Secondary dentin forms continuously throughout life, after the completion of the primary dentine and it starts at the moment that the related tooth root is completed. Hence, its amount can be used to estimate the age of an individual [14]. Secondary dentin deposition is regular when it is not under the influence of dental caries or other physical/ chemical insults to the tooth.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary dentin forms continuously throughout life, after the completion of the primary dentine and it starts at the moment that the related tooth root is completed. Hence, its amount can be used to estimate the age of an individual [14]. Secondary dentin deposition is regular when it is not under the influence of dental caries or other physical/ chemical insults to the tooth.…”
Section: Introductionmentioning
confidence: 99%
“…Bayram et al compared the mandibular condyle volume measurements done using the Cavalieri principle on CBCT images with physical volume measurements via Archimedean principle. They concluded that the Cavalieri principle is a valid tool for volume estimation of the mandibular condyle [13].There are also reports showing the use of CBCT in estimating the volume of teeth, pulp chamber, mandibular condyle, and upper airway volume [13][14][15][16][17]. In our previous study, we evaluated the accuracy of the volume assessment of the intraosseal defects using CBCT sections with a thickness of 0.2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are quantitative studies carried out on the use of CBCT systems and software in dental volumetric analysis [4,[10][11][12][13][14][15][16][17]; however, the effect of section thickness on the accuracy of the volume estimate obtained by using CBCT has not been researched in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In molars, the size of the pulp chamber reduces due to secondary dentin deposition on the roof and floor, thereby affecting the height and not width, with age. 6 In a previous study by Drusini et al, the tooth coronal index was calculated by measuring the length of coronal pulp cavity at the highest point of the pulp horn to length of crown. 13 In our study, the ratio of height of pulp chamber to height of crown root trunk was taken, which is easier to calculate compared to the method given by Drusini et al, since it is difficult to accurately appreciate coronal pulp chamber and CEJ.…”
Section: Discussionmentioning
confidence: 99%
“…5 Dental pulp size can also be used to assess the age of an individual as the size of the pulp chamber reduces with time due to deposition of secondary dentin and is not influenced by environment. 6 Kvaal et al assessed age with pulp size using periapical radiographs. 7 Since taking periapical radiograph is time consuming and difficult, the same result can be achieved by utilizing a digital orthopantogram, which is a panoramic view of the upper and lower dentition and jaw.…”
mentioning
confidence: 99%